Development of a Quantitative Loop-Mediated Isothermal Amplification Assay for the Rapid Detection of Novel Goose Parvovirus - Yang, Jing; Chen, Hao; Wang, Zhenzhong; Yu, Xianglong; Niu, Xiaoyu; Tang, Yi; Diao, Youxiang (Frontiers in Microbiology, 2017)
An infectious disease characterized with short bills and protruding tongues has attacked to meat ducks in China since March 2015, which has caused ducks poor growth and enormous economic losses to duck industry of China. It was eventually proved to be caused by parvovirus after pathogen isolation and identification. As the genomic sequence analysis showed, this pathogen shared 90.8%-94.6% of nucleotide identity with goose parvovirus (GPV), and it was called duck-origin novel goose parvovirus (N-GPV). In this study, a quantitative loop-mediated isothermal amplification (qLAMP) assay was developed for the rapid diagnosis of N-GPV. A set of four specific primers, two inner and two outer, were designed targeting at VP3 gene, which could be completed within 60 min at 65℃ in water bath or on a real-time PCR instrument for quantitative analysis. Specificity test of LAMP assay showed that there was no cross-reactivity between N-GPV and other duck pathogens, and the detection limit of qLAMP assay was 1.0×102 copies/μL. The repeatability of this method was confirmed by inter-assay and intra-assay tests with variability ranging from 0.74% to 2.25%. The results have indicated that the qLAMP assay was a simple, rapid, accurate, sensitive and specific method for detecting N-GPV, especially on field detection.